The role of Information and Communication Technology (ICT) in preaching Islam at present context - Azad Chowdhury, Md Shahnur (IIUC Studies, 2022)
Agenda-setting and representation are the media's most significant functions. The media, particularly from the West, seems to be constantly in the negative light of Islam. The fanning of Islamophobia, a type of concerted effort aimed at scaring the world of the animosity and enmity imposed by Islam, is a more recent Western media phenomenon against Islam. In response to such a striking negative portrayal of Islam, the Muslim world needs to respond. Contrary to what is commonly considered by the West, Islam means 'submission' and 'obedience' in its real nature, a religion that calls for resignation to Allah and encourages and protects the individual's peace. The primary purpose of this paper is therefore to discuss the use of a spectrum of media to disseminate information and news on the true teachings of Islam to Muslims as well as non-Muslims. The proper propagation and comprehension of Islam can be improved through the media by emphasizing the fundamental principles of Islam's teachings. IIUC Studies Vol.18, December 2021: 89-100